The industrious revolution consumer behavior and the household economy, 1650 to the present - De Vries, Jan. (Cambridge Cambridge University Press, 2008)
De Vries traces the evolution of an 'industrious revolution' that fundamentally altered the material cultures of Europe and North America.
The transformation of consumer desire in the long eighteenth century -- The origins of the industrious revolution -- The industrious revolution : the supply of labor -- The industrious revolution : consumer demand -- The breadwinner-homemaker household -- A second industrious revolution?
Keywords: Consumption (Economics) -- History; Consumers -- History